Phenotypic resistance and the dynamics of bacterial escape from phage control. - James J Bull; Christina Skovgaard Vegge; Matthew Schmerer; Waqas Nasir Chaudhry; Bruce R Levin (PLoS ONE, 2014)
The canonical view of phage - bacterial interactions in dense, liquid cultures is that the phage will eliminate most of the sensitive cells; genetic resistance will then ascend to restore high bacterial densities. Yet there are various mechanisms by which bacteria may remain sensitive to phages but still attain high densities in their presence - because bacteria enter a transient state of reduced adsorption. Importantly, these mechanisms may be cryptic and inapparent prior to the addition of phage yet result in a rapid rebound of bacterial density after phage are introduced. We describe mathematical models of these processes and suggest how different types of this 'phenotypic' resistance may be elucidated. We offer preliminary in vitro studies of a previously characterized E. coli model system and Campylobacter jejuni illustrating apparent phenotypic resistance. As phenotypic resistance may be specific to the receptors used by phages, awareness of its mechanisms may identify ways of improving the choice of phages for therapy. Phenotypic resistance can also explain several enigmas in the ecology of phage-bacterial dynamics. Phenotypic resistance does not preclude the evolution of genetic resistance and may often be an intermediate step to genetic resistance.